MMR-Varicella Vaccine and Risk of Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers from the Kaiser Permanente Vaccine Study Center, Oakland, CA, other centers in the US, and Centers for Disease Control and Prevention, Atlanta.